The influence of family socio-economic status on learning engagement of college students majoring in preschool education: The mediating role of parental autonomy support and the moderating effect of psychological capital - Qiu, Yuan; Ye, Pingzhi (Frontiers in Psychology, 2023)
Objective To explore the relationship between family socio-economic status and learning engagement of college students majoring in preschool education, as well as the mediating role of parental autonomy support and the moderating role of psychological capital. Methods A sample of 986 college students majoring in preschool education from Guangdong Province and Jiangxi Province were investigated by family socio-economic status questionnaire, learning engagement questionnaire, parental autonomy support questionnaire and psychological capital questionnaire. Results First, there was a significant positive correlation between family socio-economic status and learning engagement (β = 0.09, p < 0.05). Second, parental autonomy support played a completely mediating role between family socio-economic status and learning engagement (β = 0.05, p < 0.01). Third, the relationship between parental autonomy support and learning engagement was moderated by psychological capital, and students with high psychological capital had higher learning engagement (β = 0.24, p < 0.001). Conclusion Family socio-economic status could directly affect learning engagement, and could also indirectly affect learning engagement through psychological capital level moderating parental autonomy support. Our findings highlight the importance of creating an autonomous supportive family environment and focusing on the learning of students from low socio-economic status. Meanwhile, stimulating students’ psychological capital should be regarded as a part of education and teaching.